Functional Reception of the Qur'an and its Relevance to Quality of Life (A Study of the Kanzur Rahmah Qur'an Recitation Assembly in Depok City) - Awal, Jumadil; Ariyadi, Syamsul; Ulhaq, Ziyad (Journal Research of Social Science, Economics, and Management, 2026)
This study explores the impact of Qur’an recitation practices at the Kanzur Rahmah Qur’an Recitation Assembly in Depok on participants’ overall quality of life. In Muslim communities, the Qur’an functions not only as a sacred text but also as a guide that shapes spiritual, mental, physical, and socio-economic aspects of daily living. This research examines how intensive engagement in reading and completing the Qur’an generates positive transformation, adding new insights beyond previous studies that mainly emphasized spiritual, social, and intellectual benefits. Using the Living Qur’an framework and a descriptive qualitative approach, data were collected through observations, in-depth interviews, and document analysis, with purposive and snowball sampling used to identify key informants. The findings show that Qur’an recitation significantly affects five major areas of life: it strengthens the balance between worldly and spiritual matters, enhances acceptance of divine decree, and supports positive self-transformation; it improves mental and emotional health through better emotional control and increased family harmony; it contributes to physical well-being, with participants reporting increased vitality and recovery from certain chronic conditions; it elevates ethical and moral behavior, fostering respect for parents, teachers, and others; and it boosts socio-economic well-being by increasing gratitude, productivity, and social solidarity. Overall, the study highlights Qur’an recitation as an effective religious practice capable of improving holistic quality of life and shaping individuals and communities toward greater spiritual, mental, physical, moral, and socio-economic well-being.